Closing a Virtuous Circle: Reciprocal Influences Between Theory and Practice in Studies of Reading Intervention - Snowling, M; Hulme, C (Routledge, 2014)
The authors reflect on findings from three studies of different approaches to reading intervention (Al Otaiba et al., Denton et al., and Miller et al., all found in this issue). It is argued that the science of interventions for reading disorders is advanced and that these and other related studies provide a strong evidence base for guiding educational policy in this area. Reading interventions need to be based on theories of reading development and reading difficulty. Current causal models of reading development arguably have focused almost exclusively on the cognitive processes underlying reading development and how best to remediate deficiencies in such processes. Such models are typically silent on broader influences (motivational, attentional, and socio-cultural) on learning, however. It is concluded that future theories will need to be broadened in order to develop more effective interventions for children with a variety of reading and language learning difficulties. © 2014 Copyright Taylor and Francis Group.